Cameroon : 2013 Article IV Consultation. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper presents key discussions of Cameroon's 2013 Article IV Consultation. Economic activity in Cameroon has continued to recover gradually from the global financial crisis in 2008-2009, and inflation has remained subdued. In light of growing vulnerabilities, the report suggests to adopt a plan to reduce fuel subsidies gradually, accompanied by targeted social programs for the neediest, to free up resources for public investment. It is also necessary to accelerate resolution of distressed banks and enhance the regulatory framework to promote lending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet